An Extended Subclass of Meromorphic Multivalent Functions Involving Ruscheweyh Derivative Operator - Yassin , Nada Hameed; Jassim, Kassim A. (Iraqi Journal of Science, 2024)
In this paper, we introduce and discuss an extended subclass〖 Ą〗_p^*(λ,α,γ) of meromorphic multivalent functions involving Ruscheweyh derivative operator. Coefficients inequality, distortion theorems, closure theorem for this subclass are obtained.